$I_{\ddot{g}}$-Separation Axioms in Ideal Topological Spaces - T. Indira; S. Vijayalakshmi (International Journal of Mathematics And its Applications, 2018)
This paper mainly concentrates on the study of separation axioms in Ideal Topological spaces. In particular, we delibrate the properties of I$_{\ddot{g}}-T_{0}$ space, I$_{\ddot{g}}-T_{1}$ space, I$_{\ddot{g}}-T_{2}$ space, I$_{\ddot{g}}-Q_{1}$ space and I$_{\ddot{g}}-Q_{2}$ space.